Risk Factors and Outcomes of Occurrence of Anastomotic Leakage and Reoperations for its Management after Colorectal Surgery - Ibrahim, Amr; Gertallah, Loay M.; Naguib, Sameh Mohamed; Hemeda, Rehab; Gomaa, Ahmed Fathy; Ghoneme, Mahmoud; Sherbiny, Mahmoud; Sharaf, Ahmed Lotfy; Harb, Ola A.; Baiomy, Taha A. (Journal of Coloproctology, 2023)
Background Anastomotic leakage (AL) is still the most annoying postsurgery complication after colorectal resection due to its serious complications up to death. Limited data were available regarding differences in AL incidence, management, and consequences for different types of colorectal resection.The aim of the present work was to evaluate differences in incidence of AL, incidence of postoperative complications, and length of hospital stay in a large number of patients who underwent elective colorectal resection for management of colorectal lesions. In addition to detect when and what type of reoperation for management of AL occur after colorectal resection.Patients All 250 included patients underwent elective surgeries for colorectal resection with performance of primary anastomosis for management of colorectal neoplastic and non-neoplastic diseases in the period between May 2016 and July 31, 2021.We followed the patients for 90 days; we registered the follow-up findings.Results the rates of AL occurrence were variable after the different procedures. The lowest rate of AL occurrence was found in patients who underwent right hemicolectomy, then in patients who underwent sigmoidectomy, left hemicolectomy, transversectomy and anterior resection (p = 0.004). A stoma was frequently performed during reoperation (79.5%) which was significantly different between different procedures: 65.5% in right hemicolectomy, 75.0% in transversectomy, 85.7% in left hemicolectomy, and 93.0% in sigmoid resection (p < 0.001).Conclusion Rates, types, time of occurrence and severity of AL vary according to the type of colectomy performed and selective construction of stoma during AL reoperation is currently safely applied with comparable mortality rates for patients who did and who did not have a stoma after reoperation.
Keywords: colorectal resection; anastomotic leakage; stoma